Effect of silicon addition on the microstructure, mechanical and thermal properties of Cf/SiC composite prepared via selective laser sintering - Fu, Hua (2020)
Carbon fiber reinforced silicon carbide (Cf/SiC) composite was fabricated by infiltrating liquid silicon (Si) into the carbon preform, which was built by selective laser sintering (SLS) additive manufacturing process from the phenolic resin coated carbon fiber powder with addition of submicron Si. The effect of Si addition on the microstructures of the laser-sintered green part, carbon preform and derived Cf/SiC composite was investigated. The results show that the introduced submicron Si plays an important role in reducing porosity and average pore size of the carbon preform, and contributes to improving the microstructure homogeneity of Cf/SiC composite by reducing the size of continuous bulk carbon in the preforms. The maximum density, flexural strength and fracture toughness of the Cf/SiC composite are 2.89 ± 0.01 g/cm3, 237 ± 9.6 MPa and 3.56 ± 0.24 MPa m1/2, respectively. The coefficient of thermal expansion (CTE) of the Cf/SiC composite is approximately 5.5 × 10−6/K from 25 to 900 °C, and the thermal conductivity is in the range of 74–84 W/m·K at room temperature, while decreases to 35–40 W/m·K at 900 °C.